MDS-242 Correlation Between Myelodysplastic Syndrome and COVID-19 Infection - Abdelfatah, Rana G.; Abdelghany Shawkat, Salma; Abdelghany Ali, Menna; Ali Al Mwafy, Enaam; Moheb Mettias, Nermine (Clinical lymphoma, myeloma and leukemia, 2024)
The COVID-19 (SARS-CoV-2) pandemic had a variety of effects on patients with hematological malignancies, including diagnostic and therapeutic delays, a lack of blood supplies, and, most critically, increased risks of morbidity and death from the viral infection itself. The effects of COVID-19 on numerous particular tumors have already been detailed; however, nothing has been published on its impact on patients with myelodysplastic syndrome (MDS). This study was conducted to evaluate the epidemiology of COVID-19 in MDS patients and to estimate the prevalence of disease severity. The study was a retrospective observational study. The study included 88 MDS patients whose data was collected from all available medical records who attended the Hematology Department at Ain Shams University in Cairo between January 2020 and December 2022. Laboratory-based diagnosis of MDS patients before COVID-19 (eg, age, sex, bone marrow results, risk stratification, prognostic status of MDS, cytogenetic assessment, type of management). Evidence of COVID-19 diagnosis was also evaluated by PCR, chest x-ray, clinical presentations, type of treatment, and vaccination types and doses. A significant association was found between COVID-19 infection and the hematological presentation of the patients (P < .05). Most of our subjects (34 patients [40.5%]) fell under the category of MDSMLD. Significance was found between COVID-19 infection, the classification of MDS, the percentage of blast cells in the marrow, and the degree of dysplasia (P < .001). Significance was also reported between COVID-19 infection and the severity of MDS (P < .05). Regarding cytogenetics, the only relationships were between COVID-19 infection and deletion of chromosome 5, and patients with complex cytogenetic anomalies (P < .01 and P < .03, respectively). There was a strong correlation between COVID-19 infection and MDS severity, with a significant association between COVID-19 infection and the hematological presentation, percentage of blast cells, and the degree of dysplasia.